Scaling molecular dynamics beyond 100, 000 processor cores for large‐scale biophysical simulations. Issue 21 (17th April 2019) - Jung, Jaewoon; Nishima, Wataru; Daniels, Marcus; Bascom, Gavin; Kobayashi, Chigusa; Adedoyin, Adetokunbo; Wall, Michael; Lappala, Anna; Phillips, Dominic; Fischer, William; Tung, Chang‐Shung; Schlick, Tamar; et al.
Abstract : The growing interest in the complexity of biological interactions is continuously driving the need to increase system size in biophysical simulations, requiring not only powerful and advanced hardware but adaptable software that can accommodate a large number of atoms interacting through complex forcefields. To address this, we developed and implemented strategies in the GENESIS molecular dynamics package designed for large numbers of processors. Long‐range electrostatic interactions were parallelized by minimizing the number of processes involved in communication. A novel algorithm was implemented for nonbonded interactions to increase single instruction multiple data (SIMD) performance, reducing memory usage for ultra large systems. Memory usage for neighbor searches in real‐space nonbonded interactions was reduced by approximately 80%, leading to significant speedup. Using experimental data describing physical 3D chromatin interactions, we constructed the first atomistic model of an entire gene locus (GATA4). Taken together, these developments enabled the first billion‐atom simulation of an intact biomolecular complex, achieving scaling to 65, 000 processes (130, 000 processor cores) with 1 ns/day performance. Published 2019. This article is a U.S. Government work and is in the public domain in the USA. Abstract : The first atomistic view of an intact gene (GATA4), based on experimental HiC data, consisting of 83 kilobases of double‐stranded helical DNA wrapped around 427 nucleosomes. Including water molecules and ions, the simulation box contains over 1 billion atoms.